IMPACT OF SARCOPENIA ON THE PROGNOSIS OF PATIENTS WITH CIRRHOSIS HOSPITALIZED FOR ACUTE DECOMPENSATION OR ACUTE-ON-CHRONIC LIVER FAILURE - Leticia Macedo EIFLER; Thaís Rodrigues MOREIRA; João Pedro Pagani POSSEBON; Luis Fernando FERREIRA; Raquel de Freitas JOTZ; Ângelo Z MATTOS (Arquivos de Gastroenterologia)
ABSTRACT Background: Cirrhosis is a prevalent disease and ranks among the leading causes of death worldwide. Sarcopenia is believed to be associated with a poorer prognosis in patients with cirrhosis. Objective: To evaluate the impact of sarcopenia on the prognosis of patients hospitalized for acute decompensation of cirrhosis, with or without acute-on-chronic liver failure. Methods: This prospective cohort study evaluated patients hospitalized for acute decompensation of cirrhosis, with or without acute-on-chronic liver failure. Sarcopenia was assessed according to the European Working Group on Sarcopenia in Older People, using skeletal muscle mass analysis by bioelectrical impedance and handgrip strength testing. The data was collected between March-2019 and April-2020. Qualitative variables were presented as frequencies and percentages, and quantitative variables as means and standard deviations when symmetrical, or medians and 25th and 75th percentiles when asymmetrical. The association of sarcopenia and mortality with quantitative variables was tested using Student’s t-test or the Mann-Whitney test, while associations with qualitative variables were tested using the Chi-square test or Fisher’s Exact test. For significant associations, crude and adjusted (multivariate analysis) relative risk estimates with a 95% confidence interval were calculated using Poisson regression analysis. Results with P<0.05 were considered significant. Results: Fifty patients were included, with a mean age of 60.5 years (±10.4) and a slight predominance of men (56%). The main causes of cirrhosis were alcohol use disorder (28%) and hepatitis C (24%). The median Child-Pugh score was 8 points (7-10), and the median Model for End-stage Liver Disease score was 15 points (12.5-21). Ten patients were diagnosed with acute-on-chronic liver failure. Sarcopenia was present in 50% of the sample. Sarcopenia was present in 70.0% of patients with acute-on-chronic liver failure and in 43.2% of those without acute-on-chronic liver failure (P=0.168). Overall mortality was 48% in patients with sarcopenia and 44% in those without sarcopenia (P=1.000). In multivariate analysis, overall mortality was associated only with leukocyte count (relative risk=1.01, 95% confidence interval=1.01-1.01) and Model for End-stage Liver Disease score (relative risk=1.07, 95% confidence interval =1.03-1.10). Conclusion: In this study, sarcopenia was not associated with mortality in patients hospitalized for acute decompensation of cirrhosis, with or without acute-on-chronic liver failure. There was a non-significant trend towards a higher prevalence of sarcopenia among individuals with acute-on-chronic liver failure.